The right time for senescence - De-Carvalho, Diogo Paramos (2022)
Funding: We are truly grateful to Pedro Sousa-Vitor, Miguel Godinho-Ferreira, and Mariana AscençãoFerreira for critical reading of the manuscript. This work was supported by a FCT PhD Fellowship (PD/BD/105770/2014) to DPC, and co-funded by the FCT (PTDC/MED-NEU/30428/2017), 'la Caixa' Banking Foundation and FCT, IP, under project code HR18-00187 and SCML Melo e Castro Award (MC36-2020).